Biomecânica do comportamento alimentar de girinos de anfíbios anuros - Sousa, Verônica Thiemi Tsutae de (2016)
Individuals of the same species have morphological, physiological and behavioral characteristics that determine when and where they will exist and how they will interact with individuals of other species. The ecomorphological diversity of anuran tadpoles make them great study subjects, as the resources use patterns (ecology) and the phylogenetic relationships among species can be inferred from the phenotypic properties. The influence of contemporary factors on the structure of tadpoles communities has been intensively studied for decades, but the use patterns and partitioning of food resources, have not received the same attention from researchers. Little is known about the ecology and feeding behavior of tadpoles, including its biomechanics, the influence of abiotic factors on feeding behavior, as well as the behavioral plasticity exhibited by tadpoles in the exploitation of food resources. These issues were investigated during the PhD and the results of the work developed during the course of this period are presented in this Dissertation In the first chapter, we verified whether the carnivorous tadpole of Leptodactylus labyrinthicus would adjust their feeding kinematics to maximize food consumption when feeding on alternative food sources. Our results indicate that, depending on the food source to be explored, the tadpoles may exhibit different feeding behavior: to consume the food particles suspended in the water surface, the tadpoles exhibit the filter-feeding behavior; in contrast, to consume food particles that are attached to submerse surfaces, tadpoles use the scrape feeding behavior. Filtering and scraping feeding behaviors are quantitative and qualitatively distincts, i.e. these feeding behaviors kinematics and the shape of the oral disc during feeding show distinguishable features. In the second chapter, we tested the hypothesis that changes in the water mean temperature would have differential 15 effects on the feeding kinematics of tadpoles of two anuran species: Rhinella schneideri, whose tadpoles are benthic, and Trachycephalus typhonius, whose tadpoles are nektonic. Our results indicate that the temperature affects the kinematics of the scrape feeding behavior. However, the temperature effect on kinematics variables may depend on the species, so the changes are not in the same direction (i.e. temperature may have a positive effect on some kinematic variables but negative effects on others). Finally, in the third chapter, our aim was to verify whether the ecological and morphological influences on feeding behavior reflect the phylogenetic relationship among species.